Critical-size alveolar defect treatment via TGF-ß3 and BMP-2 releasing hybrid constructs. Issue 5 (24th March 2019) - Alici-Garipcan, Aybuke; Korkusuz, Petek; Bilgic, Elif; Askin, Kerem; Aydin, Halil M.; Ozturk, Eda; Inci, Ilyas; Ozkizilcik, Asya; Kamile Ozturk, K.; Piskin, Erhan; Vargel, Ibrahim
Abstract: In the present study a combination of Transforming Growth Factor Beta 3 (TGF-β3) and Bone Morphogenetic Protein-2 (BMP-2) loaded gelatin films sandwiched between poly (L-lactide) (PLLA)/poly (ε-caprolactone) (PCL) matrices were produced to enhance bone formation in alveolar bone defects. Osteogenic properties of tissue constructs were tested in alveolar bone defect model in rats. Bone healing was assessed by osteogenic gene expression levels of bone sialoprotein (BSP), alkaline phosphatase (ALP), osteonectin (ON, SPARC), osteocalcin (OC), runt-related transcription factor 2 (RUNX2), bone specific alkaline phosphatase (BALP) activity, histomorphometry and microtomography. Increase in osteogenic gene expression levels and BALP activity results showed that new bone formation was significantly accelerated in TGF-β3 + BMP-2 loaded scaffold group compared to growth factor free and only BMP-2 loaded groups. The micro-computed tomography (μ-CT) data from the 4 th months revealed that (TGF-β3+ BMP-2) loaded scaffolds displayed increased bone formation and was able to fulfill 84% of the defect area ( p  < 0.05). Accelerated bone formation in the S-GF-B-T group compared to that of the S-GF group at the end of the 4th month was further verified via histomorphometric analysis ( p  = 0.008). Gene expression, BALP activity, microtomography and histomorphometry analysis indicated that (TGF-β3 + BMP-2) loaded PLLA/PCL scaffolds increased the new bone formation. BMP-2 loaded scaffolds were less effective than combination of TGF-β3 and BMP-2 loaded scaffolds. These findings demonstrated that focusing on the PLLA/PCL hybrid scaffolds combined with (TGF-β3 + BMP-2) may lay the groundwork for future therapy-oriented efforts to enhance bone formation in alveolar defects.